2016
DOI: 10.1088/1757-899x/119/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Progress in development of coated indexable cemented carbide inserts for machining of iron based work piece materials

Abstract: Abstract. Increasing demands on material properties of iron based work piece materials, e.g. for the turbine industry, complicate the machining process and reduce the lifetime of the cutting tools. Therefore, improved tool solutions, adapted to the requirements of the desired application have to be developed. Especially, the interplay of macro-and micro geometry, substrate material, coating and post treatment processes is crucial for the durability of modern high performance tool solutions. Improved and novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regardless of the presence of coating on the surfaces of the insert, the authors concluded that the main reason for the poor machinabilities (flank wear) of the CGI (and NGI as well) is that the generated cutting temperatures are much higher than for the FGI. One of the main reasons to use aluminium oxide as a tool coating is because it presents a high wear resistance [3,19]. The Al 2 O 3 is characterized by excellent thermal stability, chemical inertness, relatively high hardness at elevated temperatures, and good mechanical and anti-corrosive properties [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the presence of coating on the surfaces of the insert, the authors concluded that the main reason for the poor machinabilities (flank wear) of the CGI (and NGI as well) is that the generated cutting temperatures are much higher than for the FGI. One of the main reasons to use aluminium oxide as a tool coating is because it presents a high wear resistance [3,19]. The Al 2 O 3 is characterized by excellent thermal stability, chemical inertness, relatively high hardness at elevated temperatures, and good mechanical and anti-corrosive properties [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons to use aluminium oxide as a tool coating is because it presents a high wear resistance [3,19]. The Al 2 O 3 is characterized by excellent thermal stability, chemical inertness, relatively high hardness at elevated temperatures, and good mechanical and anti-corrosive properties [19,20]. Nevertheless, the main properties of the TiO 2 include low cost, high stability, chemical inertness, biocompatibility, and non-toxicity [21].…”
Section: Introductionmentioning
confidence: 99%